Age and gender's interactive effects on learning satisfaction among senior university students. Issue 12 (1st December 2016) - Yang, Stephanie; Hsu, Wan-Chen; Chen, Hsueh-Chih
ABSTRACT: With the growing number of older adults becoming a global concern, developed countries have focused on education as a means to promote successful aging. Previous research has focused on the effects of gender and age on learning satisfaction among senior students. Nevertheless, little attention has been paid to the interactive effects of age and gender on learning satisfaction of senior university students. To investigate these effects, a learning satisfaction questionnaire was administered to 485 students enrolled in the Division of Continuing and Extension Education (DCEE) at the National Kaohsiung University of Applied Sciences in Taiwan. The data collected were subsequently examined by means of descriptive statistics and univariate analysis of variance. The results revealed that respondents were generally satisfied with the DCEE program. However, the standard deviation scores for learning satisfaction were slightly higher for males than for females. Furthermore, an interactive effect was identified between gender and age in relation to learning satisfaction. Respondents' learning satisfaction scores were higher for males than for females for the age range of 55–60. For the group aged 71 and above, females scored higher than males. However, males in the age range of 55–60 had a higher level of learning satisfaction than males aged 71 and above. Based on this study, the article identifies implications for teachers and administrators such as a need for more diverse, adaptive, and sustainable programs that enhance learner satisfaction.